Implementation of Green Airport and Digital Innovation on Service Quality and Passenger Satisfaction at Soekarno-Hatta Airport - Widyaningsih, Murti; Nugroho, Adi; Kaniati, Rika; Haryoso, Aisha Inggitha Putri (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The increasingly competitive aviation industry requires airports to improve service quality and adopt digital innovation while also responding to growing environmental concerns through the implementation of green airport practices. Passenger awareness of sustainability issues has made environmental image an important factor in shaping passenger satisfaction. This study aims to examine the effect of service quality and digital innovation on passenger satisfaction, with the green airport acting as a mediating variable at Soekarno-Hatta International Airport. A quantitative research approach was applied using Covariance-Based Structural Equation Modelling (CB-SEM) combined with Importance–Performance Analysis (IPA). Data were collected from 100 passengers through a structured questionnaire using a Likert scale and analyzed to assess both direct and indirect relationships among variables. The findings reveal that service quality has a significant indirect effect on passenger satisfaction through the green airport, indicating full mediation. In contrast, digital innovation shows no statistically significant effect on either the green airport or passenger satisfaction. Furthermore, the IPA results indicate that these environmental sustainability programs play a significant role in improving passenger satisfaction and airport image. In conclusion, strengthening green airport initiatives plays a crucial role in enhancing passenger satisfaction and supporting sustainable airport management.